Spatial distribution of Illex argentinus in San Matias Gulf (Northern Patagonia, Argentina) in relation to environmental variables: A contribution to the new interpretation of the population structuring - Crespi Abril, Augusto Cesar (2013)
Traditionally, it was assumed that major spawning activity of Illex argentinus occurs in discrete pulses along the outer-shelf/slope off Argentina/southern Brazil during late-fall/winter and that early life stages develop near the Brazil–Malvinas Confluence (BMC). However, a novel hypothesis of the population structuring of the species was proposed that states that coastal waters may be important as spawning and feeding grounds. Here, we analyzed the spatial distribution of Illex argentinus inside San Matias Gulf based on the position of the CPUE of jiggers in order to improve the knowledge of the population structuring in coastal regions. Squids were mainly concentrated on the northern region of the gulf where favorable oceanographic conditions (e.g. water stratification, chlorophyll-a concentration peaks) to feeding and spawning are present. These results provided empirical evidences that individuals of I. argentinus use Argentinean coastal waters, particularly San Matias Gulf, as permanent feeding and spawning grounds which supports the new hypothesis.